Hand eczema and steroid‐refractory chronic hand eczema in general practice: prevalence and initial treatment. (8th March 2017) - Crane, M.M.; Webb, D.J.; Watson, E.; Cunliffe, T.; English, J.
Summary: Background: The self‐reported annual prevalence of hand eczema (HE) in adults is about 10%. Incidence and prevalence data for HE, chronic HE (CHE) and steroid‐refractory CHE (SR‐CHE) in physician‐attended populations are lacking. Objectives: To estimate the prevalences of HE, CHE and SR‐CHE in a primary‐care population using a cross‐sectional design; and to estimate the incidence of each and describe initial therapy using a cohort approach. Methods: The population was all patients in the Clinical Practice Research Datalink for 2000–10, 2005–10 and 2010–11. HE was defined as any of 12 diagnoses (six specific to the hand, six for contact dermatitis). HE became CHE if any of these 12, or three additional diagnoses, occurred 90–365 days after the first HE, and if the patient was prescribed at least one course of potent topical steroids. A patient with CHE was classified as having SR‐CHE if they were (i) referred to a dermatologist and/or (ii) prescribed phototherapy, systemic immunomodulators, oral corticosteroids, alitretinoin or acitretin. Results: The 1‐year adult prevalence of HE was 0·4%. The period prevalences of SR‐CHE for 1, 5 and 10 years in adults were 0·008%, 0·036% and 0·072%, respectively; lifetime estimates were 0·071%, 0·080%, 0·098%. About one‐half of cases of CHE were steroid refractory. All conditions were more common in female than in male patients. One‐third of HE diagnoses were specific for the hand, the remainder were for contact dermatitis. The majority (62%) of newly diagnosed patients with HE were not prescribed treatment in the 12 months after diagnosis. Conclusions: Although the prevalence of HE could be 2–3 times higher than reported herein, the proportion of adults seeking medical care for HE is a fraction of those who self‐report HE. SR‐CHE is rare. Abstract : What's already known about this topic? Hand eczema (HE) by self‐report occurs in one in 10 adults in a given year. Expert opinion estimates the prevalence of severe chronic HE to be 0·5–0·7%. What does this study add? Only a small fraction of patients with self‐reported HE seek care for their condition. We estimate that < 5% of patients with HE develop chronic disease, and about one‐half of these are steroid refractory. The 10‐year period prevalence rates of adult HE and chronic HE in this population were 3·4% and 0·14%, respectively. Respond to this article Linked Comment:Agner and Nixon.Br J Dermatol 2017;176 :854–855